2016
DOI: 10.1080/14786419.2016.1195379
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated monoterpenes-rich volatile oils as potential antifungal agents for dermatophytes

Abstract: Essential oils (EOs) extracted from Lavandula luisieri and Cymbopogon citratus were tested for their antifungal activity against ten clinical isolates of dermatophytes isolated from cases of tinea pedis. Inhibition of conidial germination and antifungal drug/EO combination assay were tested on two ATCC reference strains of Trichophyton rubrum and Trichophyton mentagrophytes. EOs were characterised by high amount of oxygenated monoterpenes in their composition. Strong antifungal activity was observed for the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Furthermore, it has been shown that EOs extracted from the tea tree, eucalyptus, and thyme plants reduced Herpes simplex virus- (HSV-) 1 viral infectivity by more than 96% in an in vitro study through inactivation of virus-free particles, with the combined EO constituents more effective than the isolated counterparts [ 26 ]. Recent studies also have been pointing out the therapeutic potential of the individual constituents of EOs, such as the work of Dias and colleagues (2017), which showed a possible association between the oxygenated monoterpenes of EOs extracted from Lavandula luisieri and Cymbopogon citratus and the antifungal activity against dermatophytes [ 27 ]. This was because an inhibitory effect was observed on the conidial germination, demonstrating the strong antifungal activity of these EOs components [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that EOs extracted from the tea tree, eucalyptus, and thyme plants reduced Herpes simplex virus- (HSV-) 1 viral infectivity by more than 96% in an in vitro study through inactivation of virus-free particles, with the combined EO constituents more effective than the isolated counterparts [ 26 ]. Recent studies also have been pointing out the therapeutic potential of the individual constituents of EOs, such as the work of Dias and colleagues (2017), which showed a possible association between the oxygenated monoterpenes of EOs extracted from Lavandula luisieri and Cymbopogon citratus and the antifungal activity against dermatophytes [ 27 ]. This was because an inhibitory effect was observed on the conidial germination, demonstrating the strong antifungal activity of these EOs components [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also have been pointing out the therapeutic potential of the individual constituents of EOs, such as the work of Dias and colleagues (2017), which showed a possible association between the oxygenated monoterpenes of EOs extracted from Lavandula luisieri and Cymbopogon citratus and the antifungal activity against dermatophytes [ 27 ]. This was because an inhibitory effect was observed on the conidial germination, demonstrating the strong antifungal activity of these EOs components [ 27 ]. The mentioned studies indicate that minor constituents possess both synergistic and antagonistic activities on the major constituents, playing an important role in the overall properties of EOs on a variety of cell types.…”
Section: Introductionmentioning
confidence: 99%
“…These constituents have only been previously found in the defensive secretions of the beetle Necrodes surinamensis and in the sexual pheromone of the grape mealybug Pseudococcus maritimus [10]. The potential bioactivity of this particular plant species has been focused so far on its essential oil, for which several bioactivities have been reported; antioxidant [11,12,13]; antimicrobial [6,13,14,15,16,17] antifeedant [7,8]; ixodicidal [18]; antiparasitic [19]; and antiinflamatory [13,20]. However, information about other L. luiseri extracts is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Combination included: azoles or terbinafine or griseofulvin plus plant extracts including essential oils (19/30 studies), azoles or terbinafine or amorolfine plus immunosuppressant agents (3 studies), azoles or terbinafine plus peptides (3 studies), azoles plus disinfectants (3 studies), and other combinations including antifungal agents plus efflux pump inhibitors and statins. Checkerboard titration methodology was the most common procedure for testing the combination, followed by agar methods (i.e., disk diffusion and agar dilution) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…They act in two ways: by neutralizing free radicals (the antioxidant effect) and as anti-inflammatory agents by inhibiting the release of pro-inflammatory mediators. Secondary metabolites produced by plants are also capable of acting in a third way, as antifungal agents [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. A synergistic interaction between antifungal agents and natural products was often seen ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%